Analysis of Nurse Job Satisfaction in the Inpatient Room of Banyuasin Hospital, Banyuasin Regency, in 2023 - Oktaviana Oktaviana; Chairil Zaman; Lilis Suryani (Sean Institute, 2023)
The World Health Organisation (WHO) report from 2021 states that Universal Health Coverage (UHC) guarantees that everyone gets high-quality medical care when and when they need it, without creating any obstacles. Out of the anticipated population of 1 billion, only around 270 million individuals are expected to get health care between 2000 and 2023. The purpose of this research is to evaluate the job satisfaction of nurses working in the hospital's inpatient wards in 2023 in Banyuasin Regency. It will take place in May 2023. The 34 nurses who work in the inpatient rooms at Banyuasin Hospital make up the sample population for this quantitative, cross-sectional research. sample up to 34 respondents, and use complete sampling for sample collection. using a questionnaire for data collection and retrieval. The Chi-Square statistical test and multiple logistic regression were used in the statistical test analysis, and the findings revealed a significant relationship (p-value 0.05) between incentive variables (p=0.037), working environment conditions (p=0.001), training (p=0.000), legal protection rights (p=0.002), and rewards (p=0.016). Age (p=0.447), gender (p=0.591), education (p=0.660), work duration (p=0.448), leadership (p=1.000), chance of promotion (p=0.662), supervision (p=1.000), and punishment (p=0.731) do not correlate with one another. According to the findings of multivariate statistical analyses, the training variable was the most important factor in determining how satisfied nurses were with their jobs (p = 0.003; OR = 63.254). It is intended that nursing management at Banyuasin Hospital would be able to protect nurses legally, teach nurses to become competent nurses, pay attention to the quantity of incentives, establish a pleasant work environment, and use rewards and penalties to inspire nurses.